Pra-studi Kelayakan Sistem Hibrida PV-Baterai-PLTD di Daerah Pedesaan Wilayah Maluku - Rinaldi Maulana (Elposys: Jurnal Sistem Kelistrikan, 2024)
This research addresses the high costs and logistical challenges of diesel-based electricity generation in the rural and remote areas of Maluku. The aim is to assess the feasibility of hybridizing diesel generators with solar photovoltaic (PV) and battery energy storage systems (BESS) to reduce energy costs and environmental impacts. A tailored methodology evaluated 42 locations to determine the optimal hybrid systems. The evaluation included preliminary solar potential, electricity consumption, hybrid options, generation costs, and capital costs. Findings indicate that systems with higher renewable energy fractions are more beneficial, reducing total diesel consumption from 30.5 million L/yr to 5.8 million L/yr and Levelized Cost of Energy (LCOE) from 0.62 USD/kWh to 0.42 USD/kWh. PV sizes ranged from 150-2400 kWp with renewable energy fractions from 80-93%. This method effectively prioritizes economically and technically suitable sites.